Developing and Evaluating a Rhythm Reading Practice Kit: A Study on Learning Outcomes and Music Learners Satisfaction in Music Education Using Quantitative Analysis - Chantanasut, Thaworada (Journal of Applied Data Sciences, 2024)
This study presents the development and evaluation of a rhythm reading practice kit aimed at improving rhythm comprehension and overall student satisfaction in music education. The kit was specifically designed for students in the Western Music and Vocal Education Studies Program at Rajamangala University of Technology Thanyaburi and Nawaminthrachinuthit School, Horwang, Nonthaburi. It includes progressive exercises across multiple time signatures, enabling both guided classroom uses and self-directed practice. A quantitative research approach was adopted, utilizing pre-test and post-test assessments to measure academic improvement in rhythm reading skills, coupled with a satisfaction survey to gauge student perceptions. Findings revealed a statistically significant increase in students' post-test scores, with university students achieving a mean improvement of 18.35 points and high school students 15 points. The paired samples t-test results indicated strong significance at the .05 level, underscoring the kit's positive impact on rhythm reading proficiency. Furthermore, the student satisfaction survey highlighted high levels of approval, particularly in areas such as instructional clarity, content alignment, and ease of use for independent learning. These results suggest that the rhythm reading practice kit not only enhances students' rhythm skills but also supports their engagement and enjoyment of the learning process. The study concludes with recommendations for future research, suggesting potential digital integrations to increase accessibility and considering adaptations to address a broader range of musical skills beyond rhythm. The findings contribute to the field of music education by providing evidence of the kit's effectiveness and promoting its use as a tool to foster comprehensive rhythm education in diverse educational settings.